Bulletin de la Société de l'histoire de l'art français. - Société de l'histoire de l'art français (Paris, France); Centre national de la recherche scientifique (France) (F. de Nobele [etc.], 1875)
List of members in each volume.
Vols. for 1875-78 have a t.p. for each year; a general t.p. and index for the four years were issued at the end of the period. The first year is paged separately, second to fourth years continuously.
RILA. Répertoire international de la littérature de l'art0145-5982
Artbibliographies modern0300-466X
Avery index to architectural periodicals. Second edition. Revised and enlarged. Supplement0196-0008
Suspended 1879-1907; resumed in the latter year.
Keywords: Art, French / History / Societies, etc.; Periodicals / lcgft; Periodicals / fast / (OCoLC)fst01411641; History / fast / (OCoLC)fst01411628; Periodicals. / aat